(untitled) (World Bulletin of Public Health, 2023)
Currently, a serious attention of nephrologists and pediatricians is attracted by the fact that in the structure of chronic kidney disease (CKD) a special place belongs to the course of chronic glomerulonephritis (CGN) in children with nephrotic syndrome (NS) due to the steady progression towards chronic renal failure (CRF) and other complications leading to an increase in disability and mortality among patients. An increase in the rates of steroiddependent and steroid-resistant forms of NS is also one of the topical issues, which is determined by the high frequency of poor prognosis of diseases observed in 40-50% of patients within 5-10 years.